1969
DOI: 10.1079/bjn19690039
|View full text |Cite
|
Sign up to set email alerts
|

Mammary metabolism in lactating sows: arteriovenous differences of milk precursors and the mammary metabolism of [14C]glucose and [14C]acetate

Abstract: 1. The following techniques, which have been applied successfully to goats, were used to study mammary metabolism in lactating sows:(I) measurements of mammary arteriovenous (A-V) differences in milk precursors in the conscious undisturbed animal (five sows); (2) continuous intravenous infusion of [U-14C]glucose with concomitant arterial and mammary venous blood sampling for measurement of mammary blood flow and specific radioactivity of glucose and CO, (one sow); (3) perfusion of the isolated gland in vitro (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 23 publications
(4 reference statements)
5
79
1
1
Order By: Relevance
“…Our data indicated that concentrations of NEFA were relatively high on the day of weaning, whatever the level of feeding. This increase in plasma NEFA concentrations might result from the cessation of NEFA uptake by the mammary gland, although previous studies have shown a very low uptake of plasma NEFA by the mammary gland of the sow [28,46]. Indeed, Boyd et al [9] suggested that plasma NEFA probably contribute to milk synthesis in sows with a negative energy balance, in agreement with data from Dourmad (pers.…”
Section: Metabolitessupporting
confidence: 80%
“…Our data indicated that concentrations of NEFA were relatively high on the day of weaning, whatever the level of feeding. This increase in plasma NEFA concentrations might result from the cessation of NEFA uptake by the mammary gland, although previous studies have shown a very low uptake of plasma NEFA by the mammary gland of the sow [28,46]. Indeed, Boyd et al [9] suggested that plasma NEFA probably contribute to milk synthesis in sows with a negative energy balance, in agreement with data from Dourmad (pers.…”
Section: Metabolitessupporting
confidence: 80%
“…As the high content of these amino acids in milk greatly exceeds their accumulation via uptake by the lactating mammary gland [258,265], they must be synthesized within this organ. As in the case of proline synthesis during lactation, arginase also plays an important role in providing substrate for glutamate synthesis in the mammary gland via type II arginase, OAT and P5C dehydrogenase [249,257].…”
Section: Arginase and Glutamate Synthesismentioning
confidence: 99%
“…Glucose has been shown to be a significant amino acid carbon precursor in the lactating goat mammary gland [see Mepham, 1971]. During perfusion of the isolated sow mammary gland the incorporation of [U-14C]glucose carbon into casein was very low, alanine residues being labelled to the greatest extent [Linzell, Mepham, Annison and West, 1969]. In our experiments with [U-14C]glucose its contribution to casein amino acid synthesis resembled that in the sow in that the maximum specific activity obtained was that for alanine.…”
Section: Davis and Mephammentioning
confidence: 99%